Human resource development practitioners' perspectives on competencies: an application of American Society for Training and Development (ASTD) Workplace Learning and Performance (WLP) competency model in Malaysia - Mohd Salleh, Kahirol, author; Gloeckner, Gene W., advisor; Timpson, William M., committee member; Venneberg, Donald L., committee member; Unnithan, N. Prabha, committee member (Colorado State University. Libraries, 2012)
The intent of this research was to identify Malaysian Human Resource Development (HRD) practitioners' perceptions of competencies needed by HRD practitioners in organizations. The research was based on the American Society for Training and Development (ASTD) models for Workplace Learning and Performance (WLP) (Rothwell, Sanders, & Soper, 1999). The purpose was to assess the perceptions of Malaysian HRD practitioners in organizations regarding the importance of competencies for human resource development in organizational contexts. This study employed quantitative, cross-sectional survey, and an existing ASTD competencies instrument. Organizations were chosen based on the Federation of Malaysian Manufacturer's (FMM) database. Data for this study were collected from 144 HRD practitioners from various organizations in Malaysia who successfully completed the web-based survey. Data were analyzed using descriptive statistics, Exploratory Factor Analysis, ANOVA, t-test, and Pearson correlation. The findings of the study indicated that the Malaysian HRD practitioners perceived certain competencies as currently important and others as important in the future for their organization. The results were supported by a number of statistical findings with medium to small effect sizes. By using exploratory factor analysis, this study revealed that the Malaysian HRD practitioners perceived only 25 of the 52 competency items to be important. The results from this study have implications for the ASTD competency model and provide evidence that the competencies needed by employees and in organizations are changing over time.
Keywords: competencies; organization performance; human resource development